DEVELOPMENT OF STEAM-BASED PHYSICS LEARNING KITS AS INSTRUCTIONAL MEDIA TO IMPROVE HIGH SCHOOL STUDENTS’ CRITICAL THINKING SKILLS - Wildan Mubarok; Sherlynggar Anugrah; Iqbal Ainur Rizki (Science Education, Institut Agama Islam Negeri Ponorogo, 2026)
Critical thinking skills are essential competencies in 21st-century physics education, yet conventional instruction still tends to emphasize memorization and procedural learning. This study aimed to develop STEAM-based physics learning kits as instructional media to improve high school students’ critical thinking skills. The study employed a Research and Development (R&D) approach using the ADDIE model consisting of analysis, design, development, implementation, and evaluation stages. The participants were 35 eleventh-grade students at SMA Negeri 1 Sidoarjo selected through purposive sampling. The developed learning kits integrated Science, Technology, Engineering, Arts, and Mathematics (STEAM) components with critical thinking indicators, including analysis, inference, evaluation, interpretation, and explanation. Validation conducted by an experienced physics teacher indicated that the developed learning kits were categorized as very valid with an average score of 4.57. The implementation results showed a significant improvement in students’ critical thinking skills, reflected by the increase in average scores from 56.43 on the pretest to 82.17 on the posttest. The average N-gain score was 0.68, categorized as moderate improvement, while the paired sample t-test showed a statistically significant difference between pretest and posttest scores (p < 0.05). Students also responded positively toward the developed learning kits in terms of attractiveness, usability, and support for conceptual understanding and collaborative learning. The findings indicate that the developed STEAM-based physics learning kits effectively facilitate meaningful physics learning and support students’ critical thinking development aligned with the demands of 21st-century education.